The Investigation of the Structural Properties of 3-nitrophthalonitrile Using Spectroscopic and Quantum Chemical Computational Methods - ERYILMAZ, Serpil; AKDEMİR, Nesuhi and İNKAYA , Ersin (International Journal of Computational and Experimental Science and Engineering, 2017)
In this study, we reported structural properties of the 3-nitrophthalonitrile compound using spectral techniques such as FT-IR, 1H-NMR, 13C-NMR, X-ray single crystal diffraction. The quantum chemical computational calculations were realized with DFT/B3LYP method and 6-311G(d,p) basis set. Results of the spectral analysis were compared with theoretical molecular geometry parameters, vibrational frequencies, and chemical shift values. Some global reactivity structure parameters of the 3-nitrophthalonitrile were examined using the same method and basis set.